Treatment Planning System in Radiotherapy: A Short Review - Ting, Hii Li; Ali Rizal, Muhammad Nadiy Salamon; Othman, Siti Amira (Emerging Advances in Integrated Technology, 2023)
Treatment planning is the core in radiotherapy. The present study aimed to explore the relationship between treatment planning system and radiotherapy. Some of the important steps in radiation treatment planning system have been discussed in this paper such as patient positioning, contouring, and simulation of pre-treatment. Detailed information has been acquired by the author about dose calculations in different conditions, techniques used in beam modification such as wedge filters, bolus or multileaf collimators. Since ionising radiation creates ions in the cells of the tissues it travels through, it is frequently utilised to treat cancer cells. By taking away electrons from atoms and molecules, ions are created. It can therefore either eliminate the genes or inhibit their growth. The molecular mechanisms causing tissue damage to demonstrate that ionising radiation also chemo-selectively changes a number of biomolecules in addition to its global impact. Linear accelerator is abbreviated as LINAC. It produces high energy electron or X-ray beams using electricity. Although there are many applications for these beams, cancer treatment is one of them.